A new surface roughness measurement method based on a color distribution statistical matrix. (June 2017) - Liu, Jian; Lu, Enhui; Yi, Huaian; Wang, Menghui; Ao, Peng
Highlights: A method using color distribution statistical matrix (CDSM) to measure surface roughness is firstly proposed. The CDSM can provide a new index design method. A suit of simple device is designed to measure surface roughness. The proposed method combined with human vision system. Abstract: A ground surface roughness measurement method is proposed to address current problems in the use of machine vision technology to measure roughness: the calculations are complex, and the measurement process is largely affected by the light source. Based on the area of diffusion regions between the virtual images formed by a light source on ground surfaces with different roughness levels are different, a reference light source containing two base color is designed. Red and green color space-based color distribution statistical matrices, as well as corresponding overlap indices, are proposed. A relationship model between overlap index and roughness is constructed. The effect of light source brightness and texture direction on the relationship model is discussed based on the experimental data. The results demonstrate that the surface roughness measurement method, which is based on the overlap degree of the color image, has relatively high accuracy and a relatively wide measurement range and is, to a certain degree, robust to the brightness of the light source and the texture direction. The surface roughness measurement method has huge potential for engineering applications.